Atrial cardiopathy: a broadened concept of left atrial thromboembolism beyond atrial fibrillation. (May 2015) - Kamel, Hooman; Okin, Peter M; Longstreth, WT; Elkind, Mitchell SV; Soliman, Elsayed Z
ABSTRACT : Atrial fibrillation (AF) has long been associated with a heightened risk of ischemic stroke and systemic thromboembolism, but recent data require a re-evaluation of our understanding of the nature of this relationship. New findings about the temporal connection between AF and stroke, alongside evidence linking markers of left atrial abnormalities with stroke in the absence of apparent AF, suggest that left atrial thromboembolism may occur even without AF. These observations undermine the hypothesis that the dysrhythmia that defines AF is necessary and sufficient to cause thromboembolism. In this commentary, we instead suggest that the substrate for thromboembolism may often be the anatomic and physiological atrial derangements associated with AF. Therefore, our understanding of cardioembolic stroke may be more complete if we shift our representation of its origin from AF to the concept of atrial cardiopathy.